Performance evaluation of a QoS-aware fuzzy-based CAC for LAN access. (2016) - Inaba, Takaaki; Obukata, Ryoichiro; Sakamoto, Shinji; Oda, Tetsuya; Ikeda, Makoto; Barolli, Leonard
With the popularisation of mobile devices such as smart phones, many device communicate over wireless local area networks (WLANs). The IEEE 802.11e standard is an important extension of the IEEE 802.11 standard focusing on QoS that works with any PHY implementation. The IEEE 802.11e standard introduces EDCA and HCCA. Both these schemes are useful for QoS provisioning to support delay-sensitive voice and video applications. The EDCA uses the contention window to differentiate between high priority and low priority services. However, it does not consider the priority of users. In this paper, in order to deal with this problem, we propose and implement a fuzzy-based admission control system (FACS). We carried out many simulations to evaluate the performance of the proposed system. The simulation results show that our proposed system has a good performance.